A Project feasibility study on ULTRAGARD Anti-Carnap Device - Almirante, Jerome (College of Engineering, 1993)
The ULTRAGARD Anti-carnap device was developed by Mr. Renato L. Almirante. He came up with this invention mainly to find a solution to the problem of carnappings here in the Philippines. This invention was specifically made as to a deterent to Filipino carnappers, since some imported devices may not be adequate in the Filipino setting. Sometimes car owners here forget to switch on their security system. ULTRAGARD protects car owners from forgetting because it is automatically armed once the driver turns off the ignition. This means the car is always protected whenever the car stops. In the Philippines over half of all carnappings happen at gun point ULTRAGARD gives effective protection even at gun point. Usually car thieves steal the car as soon as the driver is about to get down from the car. With this device the driver does not have to turn on a switch or activate the device by remote control and risk getting hurt or shot by the carnapper, the driver merely gives the key and lets the carnapper drives away, leaving himself unharmed. Usually if the carnapper finds that the car won't start at the scene of the crime he will force the driver at gun point to tell him how to start the car. This device prevents this from happening because the carnapper will be able to drive away but eventually the car will stall in the middle of the road a safe distance away from you. The car will not restart and the carnapper will leave the car in the ensuing traffic jam. The target market for this product was determined to be those private car owners in the National Capital Region who don't have anti-carnap devices and who believe that such devices are necessary. From the market survey, this was found out to be 62.4% of all registered private vehicles. It was projected that of this market 3% would be the share of this product. It will be sold in car accessory shops located around Metro Manila. The technical requirements for thsi product are not at all hard to acquire and can be found right here in Metro Manila. The product is to be manufactured at #9 Sct. Delgado St., Diliman, Q.C. and the projected start-up cost is at P 1,969,451. This project was found to be financially viable based on the financial analyses conducted in this study. It shows a steady increase in net income through the projected 5-year horizon and does not show any foreseeable debt problems.